Strategi Pemerintah Kabupaten Klungkung dalam Memperkuat Ekosistem Inovasi Daerah untuk Meningkatkan Kinerja dalam Innovative Government Award (IGA) - I Gede Made Dwipa Endrayana; I Gusti Ayu Agung Dewi Sucitawathi Pinatih (Society, 2025)
The institutional transformation from Baperlitbang to the Regional Research and Innovation Agency (BRIDA) in Klungkung Regency aims to accelerate the regional innovation ecosystem to enhance national competitiveness through the Innovative Government Award (IGA). Despite dominating at the regional level in Bali, Klungkung faces challenges in breaking into the national top ten. This study aims to analyze BRIDA's management strategy in optimizing regional innovation and identify obstacles in accommodating innovation potential from the apparatus competence development path. Using a descriptive qualitative method, data were collected through in-depth interviews, participatory observation at the Innovation E-Clinic, and documentation studies. The results show that the reward strategy through "Nayaka Praja Pratibha" and technical assistance through "Innovation E-Clinic" have successfully increased the quantity of innovations. However, a "latent innovation" phenomenon was found in the form of hundreds of change projects and CPNS basic training results that have not been integrated into national reporting due to a disconnection between BRIDA and BKPSDM. This study recommends the need to integrate talent management with the regional innovation information system through cross-sectoral collaboration to minimize the leakage of regional innovation asset potential.